If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 86x + -53 = 9 Reorder the terms: -53 + 86x = 9 Solving -53 + 86x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '53' to each side of the equation. -53 + 53 + 86x = 9 + 53 Combine like terms: -53 + 53 = 0 0 + 86x = 9 + 53 86x = 9 + 53 Combine like terms: 9 + 53 = 62 86x = 62 Divide each side by '86'. x = 0.7209302326 Simplifying x = 0.7209302326
| 90-2x=4x+24 | | 4x^2+48x+27=0 | | y+9y+5=15 | | 60x-35=8 | | 18x-7i=3(6x-7u) | | 37x+50=9 | | 14x+4x^2=78 | | 14x+4x=78 | | 3z+6=4z^2+4z+1 | | 3(2-x)=3018 | | 2d+3=-10+d | | 2x^2+7x=39 | | 5c+5=4c+4 | | 200x=2x | | -10=-x-2y | | 3Q+4Q+2Q=108 | | -12=-2x-3x | | 6i(3i-9)= | | -2y=-3x-18 | | 5a^2+2-5a=0 | | 5y=-10+3y | | 15=3y-x | | -2y+4x=-8 | | 4x=6x-8 | | 9n-23=45 | | 15N-13=32 | | 2p+5=6+p | | 20=5y-4y | | x-1/3-2x-1/7-x-4/21=0 | | x/3+x+4/7=x-1 | | 5b=b+20 | | 24=7c-4c |